Alley Cropping: Teknik Budidaya untuk Mengantisipasi Bencana Alam pada Lahan Pertanian Berlereng di Daerah Objek Wisata Buya Hamka Sungai Batang Maninjau - Yulnafatmawita Yulnafatmawita; Armansyah Armansyah; Refdinal Refdinal; Zainal A. Haris (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Maninjau Village, including the tourist destination of Buya Hamka in Sungai Batang, is susceptible to natural disasters, such as landslides. It happens due to the sloping and high rainfall (> 3000 mm per year) area. The soil is prone to landslides if the sloping land is intensively cultivated for crop growth. This community engagement activity socialised and practised alley cropping techniques to manage farming in the sloping area. This method for introducing the alley cropping technique was through presentation and discussion as well as practice in the field with a farming group “Sehati”, a member of KPGH (Hamka generation youth community), and community leaders of the Nagari Sungai Batang in November 2021. A farmer cultivating red onion adopted the alley cropping method for the farm having a 19o39’ (36%) slope level with an alley width was 5 m. Gliricidia sepium and Tithonia diversifolia, known as green manure crops, were placed perpendicular to the slope of the alley fence. Gliricidia was planted every 5 m, and Tithonia between the Gliricidia at a 0.2 m distance in the alley fence.